2001
DOI: 10.1046/j.1526-4610.2001.01140.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Aspects in Migraine: Increase of IL‐10 Plasma Levels During Attack

Abstract: In the present study, 23 patients with migraine without aura were monitored during a migraine attack. Plasma levels of interleukin (IL)-4, IL-5, IL-10, and interferon-gamma were measured by enzyme-linked immunosorbent assay techniques. Interestingly, we observed low to undetectable IL-5 and IL-4 levels, whereas high IL-10 levels were seen in 52.2% of the patients. Interferon-gamma plasma levels were undetectable in all patients. After treatment with sumatriptan, 10 patients showed a subsequent decrease in IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
72
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 21 publications
(33 reference statements)
8
72
0
Order By: Relevance
“…However, it is known that cortical spreading depression, neurogenic inflammation, and craniovascular contractile dysfunction play roles in the pathophysiology of migraines [2]. During migraine attacks either with or without auras, the activated brain tissue causes the release of many peptides such as interleukins (IL-1 and IL-6), tumor necrosis factor-alpha, and adhesion molecules (intercellular adhesion molecule or vascular adhesion molecule) from the trigeminal vascular area, resulting in vasodilatation of the extraparenchymal vessels and inflammation [13,14]. It is through this mechanism that the resultant inflammation, oxidative stress, endothelial dysfunction, and hypercoagulability may lead to pathological vascular changes [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that cortical spreading depression, neurogenic inflammation, and craniovascular contractile dysfunction play roles in the pathophysiology of migraines [2]. During migraine attacks either with or without auras, the activated brain tissue causes the release of many peptides such as interleukins (IL-1 and IL-6), tumor necrosis factor-alpha, and adhesion molecules (intercellular adhesion molecule or vascular adhesion molecule) from the trigeminal vascular area, resulting in vasodilatation of the extraparenchymal vessels and inflammation [13,14]. It is through this mechanism that the resultant inflammation, oxidative stress, endothelial dysfunction, and hypercoagulability may lead to pathological vascular changes [15].…”
Section: Discussionmentioning
confidence: 99%
“…42 Other inflammatory promoters are also altered in migraineurs, including several cytokines, and some of these markers are normalized after sumatriptan. 43,44 Transient increase in soluble intracellular adhesion molecule (sICAM-1), interleukin (IL)-6, and tumor necrosis factor (TNF)-alpha can be induced by sensory neuropeptides released from activated trigeminal endings and are seen during migraine attacks. 44 Migraine is also comorbid to a number of vascular diseases.…”
Section: Possible Mechanisms Of Migraine Andmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Conflicting findings are also available regarding adhesion molecules in migraineurs. One such study showed a marked decrease in expression of intercellular adhesion molecule (ICAM)-1 and soluble (s)ICAM-1, and reduced levels of IL-4 in serum during spontaneous and nitric oxide (NO)-induced migraine attacks.…”
mentioning
confidence: 99%